AN ANALYSIS OF SYNTACTIC ERRORS MADE BY THE SECOND GRADE STUDENTS OF SMK PGRI PEKANBARU IN WRITING DESCRIPTIVE TEXT - Syari, Astuti Finis; Ras, Fakhri; Supriusman, Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is aimed to analyze what syntactic errors made by the second grade students of SMK PGRI Pekanbaru in writing descriptive text. The populations were all of the second grade students of the school in the 2018/2019 academic year. The numbers of the samples were 30 students chosen by using cluster random sampling technique. The data were collected by using written test. The data were analyzed by applying the rules of Corder (1974 in Barkhuizen, 2005) which consisted of five steps; 1) collection of sample of learner language; 2) identification of errors; 3) description of errors; 4) explanation of errors; and 5) error evaluation. Eight syntactic errors were found as the result of data analysis. They are: pronouns (25.9%), subject-verb agreements (22.7%), verb tenses and forms (14.5%), word orders (9%), articles (8.6%), prepositions (7.1%), plural nouns (6.7%), and passive voices (5.5%). The most frequent error made by the students were pronouns with a total of 66 errors (25.9%) and the least frequent error were passive voices with a total of 14 errors (5.5%). Based on the findings, there are three suggestions; 1) the students are suggested to be more concerned with the mentioned syntax items; 2) the teachers are required to give more attention regarding the students’ ability, to explain the lesson by using simple language, and to use various teaching methods in order to improve students writing abilities; and 3) future study is asked to conduct a research on the analysis of syntactic errors and the cause of the errors due to the limitation the of scope of this study.Key Words: Syntactic Error, Descriptive Text, and Writing Ability